Sustainable HRM in the face of climate change: building organizational resilience through green human capital practices - Rosyafah, Siti; Wanda Gema Prasadio Akbar Hidayat; Nitawati, Elly Yuniar (Annals of Human Resource Management Research, 2025)
Purpose: As climate change continues to pose unprecedented challenges to organizational sustainability, the role of Human Resource Management (HRM) is undergoing a critical transformation. Methodology/approach: This study investigates the integration of sustainable HRM practices particularly green human capital development as a strategic response to environmental uncertainty. Employing a mixed-methods approach, this research combines a systematic literature review with a survey of HR professionals across sectors vulnerable to climate-related disruptions. Results/findings: Findings reveal that organizations adopting green HRM frameworks such as environmentally aligned recruitment, green training, eco-driven performance management, and sustainability-based leadership development are more likely to exhibit adaptive capacities and long-term resilience. Conclusions: Furthermore, the study identifies key enablers and barriers in embedding green human capital practices into existing HR systems. Limitations: The results underscore the need for HRM to evolve beyond administrative functions and actively contribute to ecological stewardship and strategic resilience. Contribution: This research contributes to the growing discourse on sustainable organizational practices by positioning HRM as a pivotal agent in aligning human capital strategies with climate action imperatives.